The development of higher-order thinking skill-based immune system learning tools - Lissa, Lissa; Subkhi, Nur; Sunarti, Sunarti; Hamidah, Idah; Ratnasari, Anilia (Universitas Wiralodra, 2024)
Learning tools can assist teachers in facilitating achievement during the learning process. At that time, the learning tools utilized still relied upon the pre-existing 2013 curriculum, lacking the incorporation of higher-order thinking Skills (HOTS) indicators for critical thinking skills, particularly in the context of immune system material. Therefore, research was conducted to create a learning tool immunity that was based on HOTS. The objectives of this study were as follows: 1) To analyze the requirement of HOTS-based biology learning tools in the immune system material for class XI in SMA/MA; 2) To design the product development for HOTS-based biology learning tools in class XI immune system material in SMA/MA; 3) To validating HOTS-based biology learning tool products in class XI immune system material in SMA/MA. This study employed the ADDIE (Analysis, Design, Development, Implementation, Evaluation) a model for instructional design. However, this research was conducted only up to the development stage of the ADDIE model. The sample comprised five experts and three practitioners, namely biology learning experts, lecturers’ teachers, and language experts. The purposive sampling technique was employed in this research. The instruments used included product validation sheets and interview sheets. Data collection methods involved distributing product validation sheets and conducting interviews with validators. This research produces a HOTS-based immunity learning tool product which generally falls into the very valid category with a percentage of 94.56%. It means that the development product is valid for use in biology learning at the SMA/MA level.